The Development of Lesson Plan based on Conflict Cognitive Apporoach to Accomodate Student Ability in 21st Era - Rangga Alif Faresta; Muhammad Fachry; Baiq Andriani Saputri; Alpian Kurniadi (Indonesian, 2021)
RPP is an important component in supporting the successful achievement of learning objectives. The researcher intends to conduct development research to produce a lesson plan based on a feasible cognitive conflict approach. So that it can be used as an instrument of learning tools in supporting the teaching and learning process of students. This research is a research and development (R&D) with a 4D model, namely Define, Design, Develop and Disseminate. In this study, only the development stage was carried out, namely expert validation and practitioner validation of the developed instrument. Based on the expert validator's assessment, the RPP has average feasibility of all aspects of 3.47 with a very good category. While the assessment of the practitioner validator obtained the feasibility of the average value of all aspects of 3.67 with a very good category. For the Percentage of Agreement (PA), the results obtained are 90.78% from expert validators and 90.16 from practitioner validators. So it can be concluded if the lesson plans developed are reliable and appropriate to be used to support student skills based on the cognitive conflict approach in the 21st century